(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The isotopic data of atmospheric air moisture gathered from Kakinada in seaside district (Andhra Pradesh), Sagar in Central India (Madhya Pradesh), Kanpur in Indo-Gangetic plains (Uttar Pradesh), Roorkee in foot slopes of Shiwalik (Uttarakhand), Jammu in Sub-Himalayan area (Jammu and Kashmir) and Manali in Himalayan district (Himachal Pradesh) estimated in Isotope Laboratory of NIH, Roorkee and has been broke down utilizing Mat lab to discover the localterritorial part of atmospheric moisture. The aim of this paper is to define the southwest monsoon with Geospatial effect of air moisture. The isotopic examination affirms the continental and altitude effects, which were prior deciphered by the precipitation. Further, the isotopic data investigation approves the effect of local moisture on rainfall and help in settling the moisture sources in various seasons. Air moisture is utilized to investigate geospatial correlation in moisture inconstancy. This investigation further infers that the isotopic composition of air moisture can be connected for finding the beginning of monsoon. scotopic composition of GLV collected at both the destinations is thought about and it is discovered that the two isotopic spectra grossly correlate all things considered piece of the range showing that in spite of the fact that rainout process occur locally, its impact on the atmospheric water vapors can be seen over long separations. This opens up the possibility of monsoon prediction through observing of atmospheric water vapor.